Patient experience and the psychiatric discourse: Attempting to bridge incommensurable worlds - Jacob, K. S. (Indian J Psychiatry, 2015)
Divergent worldviews, incommensurable frameworks, contrasting models, distinct foci, dissimilar logic, different realities, disparate cultures, and complex patient-physician interaction impact the clinical process and problematize decision-making. Attempting to understand the disease-illness divide, engage patient perspectives, go beyond the traditional biomedical understanding of mental illness and negotiate a shared plan for treatment are serious challenges for psychiatry. The challenge for psychiatrists is to appreciate patient reality and negotiate a shared plan of treatment.